Sweat-resistant silk fibroin-based double network hydrogel adhesives - Wang, Jilei (2022)
The adhesion between flexible epidermal sensors and human skin is essential for maintaining the stable functionality of the sensors. However, it is still challenging for epidermal electronic devices to achieve durable adhesion to the surface of the skin, especially under sweaty or humid conditions. Here, we report a silk fibroin - polyacrylamide (SF-PAAm) double network (DN) hydrogel adhesive with excellent biocompatibility, strong and durable adhesion on wet surfaces, and tunable adhesive properties. The hydrophilic PAAm network greatly improves the water retention capability of the DN hydrogel and reduces the β-sheet crystalline content of the SF, leading to excellent adhesive properties of the hydrogel across a wide range of humidity. The SF-PAAm DN hydrogel adhesive can be readily integrated with different epidermal sensor arrays and performs very well in real-time on-body sweat sensing. The SF-PAAm DN hydrogels have great potential for various epidermal healthcare sensors as well as medical adhesives for other medical applications.